Diastolic blood pressure changes during episodes of autonomic dysreflexia. (3rd September 2021) - Kirshblum, Steven; Eren, Fatma; Solinsky, Ryan; Gibbs, Kathryn; Tam, Katharine; DeLuca, Robert; Linsenmeyer, Todd
Abstract : Objective: The current diagnostic criteria of autonomic dysreflexia (AD) is based solely on systolic blood pressure (SBP) increases from baseline without regard to changes in diastolic blood pressure (DBP). During urodynamics in persons with SCI at or above the sixth thoracic level (T6), we evaluated diastolic blood pressure (DBP) changes related with AD episodes. Design: Retrospective review of blood pressures recorded during urodynamics. Setting: Outpatient SCI urology program in a free standing rehabilitation center. Participants: Persons with spinal cord injury at or above the T6 level. Interventions: Urodynamic procedures performed between August 2018 to January 2019, as well as their prior testing for up to 10 years. Outcome Measures: Systolic and diastolic blood pressures were recorded during the procedure and episodes of AD defined as SBP >20 mmHg above baseline. Results: Seventy individuals accounting for 282 urodynamic tests were reviewed. AD occurred in 43.3% (122/282) of all urodynamics tests. The mean maximum SBP and DBP increase from baseline for those with AD were 35.5 ± 10.9 mmHg and 19.0±9.4 mmHg, respectively. There was a concomitant rise of DBP >10 mmHg with a SBP rise of >20 mmHg in 76.2% (93/122) of urodynamic tests. An elevation of DBP >10 mmHg was recorded in 23.8% (38/160) of urodynamics that did not have AD by the SBP definition. Conclusion: DBP increments of >10 mmHg with concurrent SBP increases of >20 mmHg occurs in the majority of AD episodes. Given the significance of cardiovascular complications in chronic SCI, further work is warranted to determine the significance of DBP elevations for defining AD.